Fine-tuning pro-angiogenic effects of cobalt for simultaneous enhancement of vascular endothelial growth factor secretion and implant neovascularization. (May 2018) - Chai, Yoke Chin; Mendes, Luis Freitas; van Gastel, Nick; Carmeliet, Geert; Luyten, Frank P.
Graphical abstract: Abstract: Rapid neovascularization of a tissue-engineered (TE) construct by the host vasculature is quintessential to warrant effective bone regeneration. This process can be promoted through active induction of angiogenic growth factor secretion or by implementation of in vitro pre-vascularization strategies. In this study, we aimed at optimizing the pro-angiogenic effect of Cobalt (Co 2+ ) to enhance vascular endothelial growth factor (VEGF) expression by human periosteum-derived mesenchymal stem cells (hPDCs). Simultaneously we set out to promote microvascular network formation by co-culturing with human umbilical vein endothelial cells (HUVECs). The results showed that Co 2+ treatments (at 50, 100 or 150 µM) significantly upregulated in vitro VEGF expression, but inhibited hPDCs growth and HUVECs network formation in co-cultures. These inhibitory effects were mitigated at lower Co 2+ concentrations (at 5, 10 or 25 µM) while VEGF expression remained significantly upregulated and further augmented in the presence of Ascorbic Acid and Dexamethasone possibly through Runx2 upregulation. The supplements also facilitated HUVECs network formation, which was dependent on the quantity and spatial distribution of collagen type-1 matrix deposited by the hPDCs. When applied to hPDCs seeded onto calcium phosphate scaffolds, the supplements significantly induced VEGF secretion in vitro, and promoted higher vascularization upon ectopic implantation in nude mice shown by an increase of CD31 positive blood vessels within the scaffolds. Our findings provided novel insights into the pleotropic effects of Co 2+ on angiogenesis (i.e. promoted VEGF secretion and inhibited endothelial network formation), and showed potential to pre-condition TE constructs under one culture regime for improved implant neovascularization in vivo . Statement of Significant: Cobalt (Co 2+ ) is known to upregulate vascular endothelial growth factor (VEGF) secretion, however it also inhibits in vitro angiogenesis through unknown Co 2+ -induced events. This limits the potential of Co 2+ for pro-angiogenesis of tissue engineered (TE) implants. We showed that Co 2+ upregulated VEGF expression by human periosteum-derived cells (hPDCs) but reduced the cell growth, and endothelial network formation due to reduction of col-1 matrix deposition. Supplementation with Ascorbic acid and Dexamethasone concurrently improved hPDCs growth, endothelial network formation, and upregulated VEGF secretion. In vitro pre-conditioning of hPDC-seeded TE constructs with this fine-tuned medium enhanced VEGF secretion and implant neovascularization. Our study provided novel insights into the pleotropic effects of Co 2+ on angiogenesis and formed the basis for improving implant neovascularization.